2020
DOI: 10.1111/vop.12819
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two rebound tonometers in healthy horses

Abstract: Objective To obtain a reference range for evaluation of intraocular pressure (IOP) in horses using Tonovet Plus®, to compare the IOP readings obtained with Tonovet® and Tonovet Plus®, and to evaluate the repeatability of readings. Animals studied and Procedures Intraocular pressure of 30 client‐owned horses (60 eyes) with no signs of illness or ocular disease was evaluated using Tonovet® and Tonovet Plus® rebound tonometers. Horses’ mean age was 10.7 (range 6‐17) years. Triplicate measurements were performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
4
16
1
Order By: Relevance
“…This finding was also reported by Knollinger et al (2005) 34 . It has been recommended that the same type of tonometer should be used when IOPs must be repeated 33,34 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding was also reported by Knollinger et al (2005) 34 . It has been recommended that the same type of tonometer should be used when IOPs must be repeated 33,34 …”
Section: Discussionsupporting
confidence: 82%
“…Data from this study revealed a significant difference between the two rebound tonometers (TonoVet and TonoVet Plus) with the TonoVet measuring mean IOP slightly higher than those recorded by TonoVet PLUS. A recent study by Mustikka et al 33 (2020) reported opposite results: In this study, the TonoVet PLUS measured a significantly higher mean IOP in horses than the TonoVet. Operator variables or environmental conditions (heat or humidity) related to geography or time of year could also have affected IOP values.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In fact, the IOP was significantly increased (p = .02) in phase 2 (at the baseline and T2) compared with phase 1. The IOP was within normal range values 14,15 at these times, and there was no effect of the treatment. For these reasons, the significant difference was not considered clinically significant and could be attributable to the measurement technique or to the daily variation of the IOP.…”
Section: Daily Feces Productionmentioning
confidence: 76%
“…In 3/48 eyes, large iris cysts were in contact with the endothelium leading to localised corneal oedema. Based on the treating veterinarian's assessment, intraocular pressure (IOP) was measured in 10 horses and was within normal limits (16–30 mmHg) in all of them 24,25 …”
Section: Resultsmentioning
confidence: 99%